Effect of Bovatec, Oxytetracycline (OTC), Bovalec Plus OTC and Rumensin-Tylan combination on feedlot performance and liver abscess control in finishing steers - B. Lee; S. Laudert (Kansas Agricultural Experiment Station Research Reports, 1984)
Adding Bovatec, OTC, Bovalec plus OTC or Rumensin-Tylan to finishing steer diets did not significantly improve average daily gain in the 133 day feeding period, but did improve (P<.05) feed to gain ratios. The Rumensin-Tylan combination was the only treatment that reduced (P<.05) liver abscess incidences.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Performance; Feedlot; Liver abscess